GLOCALIZATION OF ARABIC LANGUAGE MODULE UPT LANGUAGE UIN RADEN MAS SAID SURAKARTA - Rio Kurniawan (2025)
This article departs from the vision and Glocalization program launched by UIN Raden Mas Said Surakarta as campus development, Glocalization of globalization by precipitating local wisdom. Where local values in Soloraya which is also the location of UIN RM Said can be raised to the global level, and vice versa. Departing from the background above, this research has an important value to be carried out, namely looking at the development of practicum modules or Arabic language training courses UPT Bahasa UIN Raden Mas Said Surakarta. With the results of the research as follows. First, Glocalization of Arabic modules is very necessary which previously used modules with material or readings from abroad so that students find it difficult to understand, with the development of modules with adapted material and then developed based on local wisdom. Second, the material is in accordance with the local which consists of two modules with details of module 1: Introduction to campus, History of UIN Raden Mas aid Surakarta, UPT Bahasa, Raden Mas Said, shop, Islamic Studies, Arabic, Technology, and Health while module 2: At Ta'aruf, Al Usroh, As Sakan, Ad Dirosah, Fil Maqsof, Fil Maktabah, Al Hiwayah, As Safar, Al Amal, Al Ilmu An Nafi'. Third, the author of the Arabic module is a practicum tutor or language training course who is also a question maker so that he can know the process of preparing modules, materials to evaluation in the process involved in compiling, implementing and evaluating their effectiveness in the hope that the modules can be used both for the academic community and external UIN Raden Mas Said Surakarta